Error-Related Negativity-Based Robot-Assisted Stroke Rehabilitation System: Design and Proof-of-Concept - Kumar, Akshay; Gao, Lin; Li, Jiaming; Ma, Jiaxin; Fu, Jianming; Gu, Xudong; Mahmoud, Seedahmed S.; Fang, Qiang (Frontiers in Neurorobotics, 2022)
Conventional rehabilitation systems typically execute a fixed set of programs that most motor-impaired stroke patients undergo. In these systems, the brain, which is embodied in the body, is often left out. Including stroke patients’ brains in the control loop of a rehabilitation system can be worthwhile as the system can be tailored to each participant and, thus, be more effective. Here, we propose a novel brain-computer interface (BCI) based robot-assisted stroke rehabilitation system (RASRS), which takes inputs from the patient’s intrinsic feedback mechanism to adapt the assistance level of the RASRS. The proposed system will utilize the patients’ consciousness about their performance decoded through their error-related negativity signals. As a proof-of-concept, we experimented on twelve healthy people in which we recorded their EEG signals while performing a standard rehabilitation exercise. We set the performance requirements beforehand and observed participants' neural responses when they failed/met the set requirements and found a statistically significant (p < 0.05) difference in their neural responses in the two conditions. The feasibility of the proposed BCI-based RASRS was demonstrated through a use-case description with a timing diagram and meeting the crucial requirements for developing the proposed rehabilitation system. The use of a patient’s intrinsic feedback mechanism will have significant implications for the development of human-in-the-loop stroke rehabilitation systems.